2004
DOI: 10.1103/physrevlett.93.171103
|View full text |Cite
|
Sign up to set email alerts
|

F60eAnomaly in a Deep-Sea Manganese Crust and Implications for a Nearby Supernova Source

Abstract: A nearby supernova (SN) explosion in the past can be confirmed by the detection of radioisotopes on Earth that were produced and ejected by the SN. We have now measured a well resolved time profile of the 60Fe concentration in a deep-sea ferromanganese crust and found a highly significant increase 2.8 Myr ago. The amount of 60Fe is compatible with the deposition of ejecta from a SN at a distance of a few 10 pc. The well defined time of the SN explosion makes it possible to search for plausible correlations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
284
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(312 citation statements)
references
References 32 publications
23
284
2
Order By: Relevance
“…60 Fe radioactivity from (probably) the same sources which create 26 Al provide a global massive-star population diagnostic of the interior structure of massive stars. The discovery of 60 Fe also in ocean crust material [67] underlines the role of such long-lived radioactive isotopes as tools to study cosmic nucleosynthesis, in particular also addressing the aspect of how core-collapse supernovae spread their ejecta in their surroundings. 26 Al emission from nearby regions is bright enough so it can be located relative to its sources.…”
Section: Discussionmentioning
confidence: 99%
“…60 Fe radioactivity from (probably) the same sources which create 26 Al provide a global massive-star population diagnostic of the interior structure of massive stars. The discovery of 60 Fe also in ocean crust material [67] underlines the role of such long-lived radioactive isotopes as tools to study cosmic nucleosynthesis, in particular also addressing the aspect of how core-collapse supernovae spread their ejecta in their surroundings. 26 Al emission from nearby regions is bright enough so it can be located relative to its sources.…”
Section: Discussionmentioning
confidence: 99%
“…Eu, as the best observed (almost pure) r-process element, shows a big scatter in [Eu/Fe] at low metallicities, indicating that the r-process is a rare event and it takes longer to arrive at average values than for elements produced in frequent events like supernovae. A second indication that the r-process is produced in sites of rare occurence is the recent addition of 60 Fe found in deep-sea sediments probably due to the last nearby CCSN about 2 million years ago, while 244 Pu has not been added at this point in time and its low value must come from rarer and earlier events which permitted for some subsequent decay [30,76] A final indication that supernovae (and at low metallicities these are regular CCSNe) are not responsible for the heavy r-process elements is the non-correlation of r-process elements with the Fe-group, which is produced by CCSNe [11].…”
Section: Observational Constraintsmentioning
confidence: 99%
“…60 Fe (half-life 2.6 × 10 6 y) is an example for (a) and goes back to hydrostatic burning stages [34,37,81]. Recent findings show that it can witness the last CCSNe near the solar system about 2 to 3 million years ago [30,76]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that extraterrestrial debris might be taken into manganese encrustations as evidenced by its 3 He/ 4 He isotopic ratio (Sano et al, 1985;Basu et al, 2006). Recently, the so-called extinct nuclides, such as 60 Fe (T 1/2 = 1.51 × 10 6 yr) and 244 Pu (T 1/2 = 8.08 × 10 7 yr) that are not expected in the solar system because their half-lives are sufficiently shorter than the age of the solar system, were found in a manganese encrustation by Knie et al (1999), Wallner et al (2000), Knie et al (2004), and Wallner et al (2004). Knie et al (2004) found a highly significant increase in the 60 Fe concentration around 2.8 Myr ago in a dated deep-sea manganese crust by using an accelerator mass spectrometer (AMS).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the so-called extinct nuclides, such as 60 Fe (T 1/2 = 1.51 × 10 6 yr) and 244 Pu (T 1/2 = 8.08 × 10 7 yr) that are not expected in the solar system because their half-lives are sufficiently shorter than the age of the solar system, were found in a manganese encrustation by Knie et al (1999), Wallner et al (2000), Knie et al (2004), and Wallner et al (2004). Knie et al (2004) found a highly significant increase in the 60 Fe concentration around 2.8 Myr ago in a dated deep-sea manganese crust by using an accelerator mass spectrometer (AMS). Wallner et al (2004) attempted to detect 244 Pu in 120 g of a fallout-free part of a deep-sea manganese crust using an AMS.…”
Section: Introductionmentioning
confidence: 99%